PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI KANTOR KECAMATAN BENER PURWOREJO - Rimas Cahyo Saputro; Dian Marlina Verawati (Transpublika Publisher, 2022)
Employee performance is a component used to measure the success of an employee in completing his work. This study aims to determine and analyze the effect of work motivation and work discipline on the performance of employees at the Bener Purworejo District Office. This research method uses a quantitative research type, this survey uses primary data that is processed from 40 respondents as the sample, and in collecting data, the researcher uses a method of distributing questionnaires to the respondents. After the data is collected, it will be analyzed using multiple linear regression analysis using SPSS. The results of this study indicate that motivation and work discipline simultaneously have a significant effect on employee performance. The work discipline has a positive and significant effect on employee performance, while work motivation has a positive but not significant effect on employee performance. From the results of the determination test, it can be said that, the influence of work motivation and work discipline on employee performance is 18.4%, so the influence of other variables on employee performance outside this study is 81,6%.